Publishing and presenting clinical research - Browner, Warren S. (Lippincott Williams & Wilkins, 2012)
Uses hundreds of examples, tables and figures to show how to produce successful abstracts, posters, oral presentations, and manuscripts for publication. This book also serves as a companion to the popular text, "Designing Clinical Research"